Empowering teachers to create learning animation videos with an assessment as learning approach - Rukli Rukli; Nurhikmah H; Nurindah Nurindah (Universitas Pendidikan Indonesia, 2023)
The technological age dragged other fields to use technology, including video games. As a result, video games are increasingly popular with school children, especially elementary school children. Even though teachers are the front line to divert children's attention from playing games to learning animations, the teacher working group of Rayon 18 South Sulawesi has limitations in making interesting videos even though they have carried out several activities. Therefore, empowering teachers is a solution to apply research results by participating in training to make learning animation videos using the assessment as a learning approach. The activity was attended by 35 elementary school teachers from the rayon for one day with three sessions. The direction of the line of training participants' understanding ability increases where the post-test score is higher than the pre-test. The correlation between questions shows a consistent increase. Likewise, this increases teacher skills in installing applications, applying video applications to create videos, and increasing teacher skills in creating animated learning videos. Teachers feel satisfied receiving the benefits of taking part in training in making learning animation videos. Therefore, teachers can increase creativity by creating learning animation videos so students are more interested and focused on learning. Abstrak Era teknologi menyeret bidang lain untuk menggunakan teknologi termasuk video game. Alhasil, video game semakin digemari oleh anak-anak sekolah, khususnya anak sekolah dasar. Meskipun guru merupakan garda terdepan untuk mengalihkan perhatian anak dari bermain game ke bermain animasi pembelajaran, namun Kelompok Kerja Guru Rayon 18 Sulawesi Selatan memiliki keterbatasan dalam membuat video yang menarik meskipun telah melakukan beberapa kegiatan. Oleh karena itu, pemberdayaan guru menjadi solusi untuk menerapkan hasil penelitian dengan mengikuti pelatihan pembuatan video animasi pembelajaran dengan pendekatan asesmen sebagai pembelajaran. Kegiatan diikuti oleh 35 orang guru SD rayon selama satu hari dengan tiga sesi. Arah garis kemampuan pemahaman peserta diklat meningkat dimana skor post-test lebih tinggi dibandingkan pre-test. Korelasi antar pertanyaan menunjukkan peningkatan konsisten. Begitu pula dengan peningkatan keterampilan guru dalam menginstal aplikasi, peningkatan keterampilan guru dalam menerapkan aplikasi video untuk membuat video, dan peningkatan keterampilan guru dalam membuat video animasi pembelajaran. Guru merasa puas menerima manfaat mengikuti pelatihan pembuatan video animasi pembelajaran. Oleh karena itu, guru dapat meningkatkan kreativitas untuk membuat video animasi pembelajaran agar siswa tertarik belajar dan lebih fokus dalam belajar. Kata Kunci: Animasi pembelajaran; pemberdayaan guru; penilaian sebagai pembelajaran